Challenges in risk analysis for science and engineering : development of a common language - Temple, Tracey J.; Ladyman, Melissa K.; Institute of Physics (Great Britain) (Bristol [England] (No.2 The Distillery, Glassfields, Avon Street, Bristol, BS2 0GR, UK) : IOP Publishing, 2022)
The aim of this reference text is to provide a common language and consistent approach to risk assessment across science and engineering disciplines through the collation of detailed, real examples and scenarios. Examples are drawn from a variety of industries and cover key risk topics such as tolerability, data collection, hazard identification and hazard interpretation. The approaches communicate common challenges and are compared and contrasted, with a particular focus on the terminology used. The book is essential reading for scientists and engineers that undertake risk assessment, including industry practitioners, researchers in academia and those with a general interest in improving risk assessment processes. It is also a valuable reference for science and engineering students that regularly undertake risk assessments or study courses on risk assessment.
Introduction to challenges in Risk Analysis for science and engineering: development of a common language -- 1. An introduction to risk analysis for scientists and engineers / F. Persico and E. Gutierrez Carazo -- 2. On the tolerability of risk, public and private / M.R. Williams -- 3. Storage of military ammunition and explosives--risk evaluation and hazard management / D. Skelly -- 4. The application of systems thinking to risk assessment : left shifting safety / D. Holley, P. Gill, N. Mai and R. Vrcelj -- 5. Influence of automation on human factor integration in risk assessment systems / B. Thawani, R. Critchley and R. Hazael -- 6. Minimising the risks to decision-making by selecting representative experimental methods for environmental science research / E. Gutierrez Carazo, F. Persico, M. Ladyman, T. Temple and F. Coulon -- 7. The importance of the conceptual site module in the assessment of land contamination / P. Burden, A.-M. Deloughry and J. Morgan -- 8. Land Release : a risk management approach for mine action / R. Evans -- 9. Risk assessment and management at a heritage site / G. Hooper -- 10. Amazonian non-timber forest products and ways forward to ensure their sustainability at low risk : acai case study / K.K.L. Yamaguchi, J. Campos Zeballos, S. Janzen, E.B.F. Galante and V.F. Veiga-Junior -- 11. Development of a risk matrix for low-cost engineering solutions : a systematic approach / L Roberts, R Critchley, D Salberg, S Bloodworth-Race and R Hazael -- 12. Assessing the academic and experiential risk to students from the transition to hybrid and online delivery / M. Ladyman, T. Temple and A. Temple -- 13. Practical application of a decision framework to mitigate environmental risks posed by the treatment of explosive contaminated wastewater / W. Gilroy-Hirst, J. Padfield, M. Ladyman, F. Coulon and T. Temple -- 14. Risk recognition and continuous risk management / Z. Rustom -- 15. Conclusion : challenges in risk analysis / M. Ladyman and T. Temple.
"Version: 20221001"--Title page verso.
Includes bibliographical references.
Scientists and engineers that undertake risk assessment, including industry practitioners, researchers in academia and those with a general interest in improving risk assessment processes.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader, EPUB reader, or Kindle reader.
Keywords: Technology -- Risk assessment; Risk assessment; Risk assessment; Education and outreach